SPORT FOR SOCIAL COHESION: SOME CRITICAL CONSIDERATIONS - Moustakas, Louis (ASEAN Journal of Sport for Development and Peace, 2024)
In recent decades, social cohesion has garnered significant attention as a key policy objective, with sport increasingly promoted as a potentially effective, low-cost tool to achieve this goal. Despite its growing popularity, the concept of social cohesion, particularly within the sport for development (SFD), faces substantial criticisms regarding its definition and implementation. A primary concern is the individual-centric approach prevalent in many SFD initiatives, which assumes that improving individual skills and attitudes will naturally translate to broader social cohesion. This approach typically targets marginalized groups such as migrants, refugees, and minorities, expecting these individuals to act as agents of change within their communities. However, this strategy often fails to address the structural and systemic factors that influence or limit social cohesion, placing undue responsibility on vulnerable individuals without sufficient support for long-term community impact. Critiques of this individual focus highlight the need for more participatory and political approaches that engage a broader spectrum of community members and stakeholders. Recent efforts in the SFD sector have begun to explore methodologies like co production, participatory action research, and Living Labs, which involve community members in the design and implementation of programs. These approaches aim to foster sustainable outcomes by addressing community needs and promoting engagement at both community and organizational levels. Moreover, SFD organizations are encouraged to extend their role beyond program implementation to active advocacy for systemic change. By leveraging their insights from community interactions, these organizations can influence policy and advocate for long-term solutions that promote social cohesion. This requires a shift in perspective, recognizing the socio political role that SFD can play in addressing broader societal issues